1920
DOI: 10.3181/00379727-17-38
|View full text |Cite
|
Sign up to set email alerts
|

The relation of the portal blood to liver maintenance

Abstract: The relation of the portal blood to liver maintenance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

1927
1927
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 0 publications
3
18
0
Order By: Relevance
“…This abrupt change in the path of the blood is well tolerated by the organism, as an abundant experience has shown (13); and in the course of the present work it has been observed to have no effect on the carotid pressure, lgeedless to say the necessary operation was performed with the least possible trauma and exposure of the viscera, only a short segment of the vein being dissected free for ligation. * The hepatic artery, in special, was not touched; and it was seen by direct inspection to continue to beat strongly.…”
Section: The Service Rendered By the Hepatic Arterysupporting
confidence: 56%
“…This abrupt change in the path of the blood is well tolerated by the organism, as an abundant experience has shown (13); and in the course of the present work it has been observed to have no effect on the carotid pressure, lgeedless to say the necessary operation was performed with the least possible trauma and exposure of the viscera, only a short segment of the vein being dissected free for ligation. * The hepatic artery, in special, was not touched; and it was seen by direct inspection to continue to beat strongly.…”
Section: The Service Rendered By the Hepatic Arterysupporting
confidence: 56%
“…In rabbits, it has been demonstrated that ligation of one branch of the portal vein leads to atrophy of the ischemic portion and hypertrophy of the vascularized region of the liver [11]. In human livers obtained at explant, segmental resection, or autopsy, it has been shown that apoptosis, focal atrophy, and nodular hyperplasia of the liver are associated with acute and healed portal vein thrombosis [12].…”
Section: Pathogenesismentioning
confidence: 99%
“…As there pointed out, the parenchymal cells of the liver compete with one another for existence (12); and the lobular capillaries converge and progressively unite on the way to the venous center, the result being that the further a ceU is from the blood source the greater is the quantity of blood passing it. Thus opportunity is equalized.…”
Section: The Gradient In the Mammalian Diaphragmmentioning
confidence: 99%